A review of the methodological misconceptions and guidelines related to the application of structural equation modeling: A Malaysian scenario - Mumtaz Ali, Memon; Hiram, Ting; Ramayah, T.; Chuah, Francis; Cheah, Jun-Hwa (Sarawak Research Society (SRS), 2017)
Although structural equation modeling (SEM) is a powerful statistical technique, understanding its methodological assumptions before data analyses is essential to attaining more robust results. In this editorial, we outline four major methodological issues which are related to the application of SEM in Malaysia along with their respective guidelines. These issues include 1) probability and non-probability sampling, 2) pre-testing and pilot study, 3) CB-SEM and PLS-SEM, and 4) exploratory and confirmatory factor analysis. We also recommend the steps that the local research community, especially the postgraduate students, should consider taking to keep themselves up-to-date with methodological advances and to make informed decisions about the use of SEM. This humble effort will help to clarify the confusion and doubts many lecturers and postgraduate students in Malaysia might have, and provide directions to what they should do in a practical manner.